Neural Plasticity of Mild Tinnitus: An fMRI Investigation Comparing Those Recently Diagnosed with Tinnitus to Those That Had Tinnitus for a Long Period of Time - Jake R. Carpenter-Thompson; Sara A. Schmidt; Fatima T. Husain (Neural Plasticity)
Objectives. The aim of the study was to compare differences in neural correlates of tinnitus in adults with recent onset and others who had the disorder for longer than a year. Design. A total of 25 individuals with tinnitus were divided into groups based on the amount of time for which they had experienced tinnitus: <1 year (RTIN) or >1 year (LTIN). Subjects underwent an fMRI scan while listening to affective sounds from the International Affective Digital Sounds database. Resting state functional connectivity data were also collected. Results. The RTIN group recruited the posterior cingulate and insula to a greater extent than the LTIN group when processing affective sounds. In addition, we found that the LTIN group engaged more frontal regions when listening to the stimuli compared to the RTIN group. Lastly, we found increased correlations between the default mode network and the precuneus in RTIN patients compared to LTIN at rest. Conclusion. Our results suggest that the posterior cingulate and insula may be associated with an early emotional reaction to tinnitus in both task and resting states. Over time, tinnitus patients may recruit more frontal regions to better control their emotional response and exhibit altered connectivity in the default mode network.